Eternal mothers, whores or witches: the oddities of being a woman in politics in Zimbabwe. Issue 4 (1st October 2020) - Ncube, Gibson
Abstract: In the country where I come from, Zimbabwe, participation in politics and decision-making is very much a masculine affair. Women occupy peripheral positions in which they are expected not to decentre male dominance. Through cultural practices inflated with religious beliefs, women have often been relegated to the domestic space of the home in which their agency is reduced to executing banal household chores. Positionally, as a male academic, I am fully aware of my privileged position and the multiplicity of rights and liberties that accompany such a position. Even from such a position of privilege, I am not oblivious of the structural and systemic machinations that continue to hinder women from fully taking part in politics, not simply as voters, but more importantly as active holders of positions of power and authority. In this article i am interested in how women in politics in Zimbabwe are framed either as eternal mothers, 'whores' or witches who use their sexuality and bodies to get ahead in politics. Although I focus on Grace Mugabe (former First Lady) and Joice Mujuru (former Vice President), women politicians face similar treatment regardless of the political party or party faction that they belong to. I argue that as long as women politicians play according to the patriarchal and masculinist script, they are endearingly referred to as 'Amai' (Shona for mother). The moment that they stray from the patriarchal script and they seek to impose themselves as agentive political characters, they are referred to as 'hure' (Shona for whore or prostitute) or 'muroyi' (Shona for witch). Drawing on the concept of the "unruly African woman" that Chigumadzi articulates in her book These Bones Will Rise Again, and further develops in her essay "In Zimbabwe, the enduring fear of single women", I contend that the trope of the whore is itself a productive imagining of women who refuse to toe the line of patriarchal dictates of feminine visibility and uprightness.